2010
DOI: 10.1016/j.mambio.2009.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in molar outline of bank voles: An effect of wear?

Abstract: Morphometric characters can be of use for elucidating the evolutionary history of species by providing an insight into the selective pressure related to the character of interest, and by allowing integration of fossil specimens. This potential interest of phenotypic characters, however, depends on how much other sources of variation, such as the lifehistory of the animal, may blur an evolutionary signal. For instance, age structure varies along the year, causing in turn various assemblages of wear stages in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…We found morphological variation in the first upper molars of southern red‐backed voles to be strongly affected by tooth wear. Previous studies have also identified a major effect of wear on tooth size and shape in the bank vole Myodes glareolus (Fominykh et al ., ; Guérécheau et al ., ; Ledevin et al ., ). According to these authors, voles trapped in different seasons (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found morphological variation in the first upper molars of southern red‐backed voles to be strongly affected by tooth wear. Previous studies have also identified a major effect of wear on tooth size and shape in the bank vole Myodes glareolus (Fominykh et al ., ; Guérécheau et al ., ; Ledevin et al ., ). According to these authors, voles trapped in different seasons (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth wear has been recognized as a major source of morphological variation in arvicoline teeth (Fominykh et al ., ; Guérécheau et al ., ; Ledevin et al ., ), acting as a confounding factor when analysing covariates of tooth morphology. Therefore, we developed a tooth wear classification method based on the number of closed dentinal space isthmuses (Abe, ), continuity of the enamel crest and presence of dentin in the re‐entrant angles (Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…These teeth were chosen because UM1 and LM1 are the most widely used teeth in paleontological and biogeographic studies (Kitahara, 1995; Chaline et al ., 1999; Luo et al ., 2004; Martin, Crockett & Marcolini, 2006; Tougard et al ., 2008). We added UM3 because a few studies have used it for systematic purposes (Kaneko, 1992) and evolutionary studies (Barnosky, 1993), and because this tooth displays a large intraspecific variation (Bauchau & Chaline, 1987; Guérécheau et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We note however that these maps are congruent concerning the location of the main area of transition between the clusters and that the analysis based on spatial information is graphically more efficient at displaying the location of this transition. The bank vole molar shape has been shown to display a large variation even within populations, due to wear and developmental factors (Guérécheau et al, 2010;Ledevin et al, 2010b). This may render even clear cut inter-specific boundaries difficult to detect.…”
Section: The Myodes Data-setmentioning
confidence: 99%